Phospholipid Signaling Is a Component of the Salicylic Acid Response in Plant Cell Suspension Cultures - Rodas-Junco, Beatriz A.; Nic-Can, Geovanny I.; Muñoz-Sánchez, Armando; Hernández-Sotomayor, S. M. Teresa (International journal of molecular sciences, 2020)
Salicylic acid (SA) is an important signaling molecule involved in plant defense. While many proteins play essential roles in SA signaling, increasing evidence shows that responses to SA appear to involve and require lipid signals. The phospholipid-generated signal transduction involves a family of enzymes that catalyze the hydrolysis or phosphorylation of phospholipids in membranes to generate signaling molecules, which are important in the plant cellular response. In this review, we focus first, the role of SA as a mitigator in biotic/abiotic stress. Later, we describe the experimental evidence supporting the phospholipid–SA connection in plant cells, emphasizing the roles of the secondary lipid messengers (phosphatidylinositol 4,5-bisphosphate (PIP2) and phosphatidic acid (PA)) and related enzymes (phospholipase D (PLD) and phospholipase C (PLC)). By placing these recent finding in context of phospholipids and SA in plant cells, we highlight the role of phospholipids as modulators in the early steps of SA triggered transduction in plant cells.